Performance of basmati rice (Oryza sativa) through organic source of nutrients - MAHAJAN, G; GILL, M S; DOGRA, B (The Indian Journal of Agricultural Sciences, 2012)
Grain yield of basmati rice improved with organic source of nutrients as compared to recommended level of N and untreated control. GLM (5 tonnes/ha) + VC (2.5 tonnes/ha), GLM (10 tonnes/ha), neem cake (2.5 tonnes/ha) caused 20.2, 16.7 and 15.2% higher grain yield than recommended level of N respectively. So, it was concluded that GLM (10 tonnes/ ha) or GLM (5 tonnes/ha) + VC (2.5 tonnes/ha) or neem cake (2.5 tonnes/ha) are an ideal organic nutrition module/ dose to meet the nutritional requirement of basmati crop and is best alternative to inorganic fertilizer without significant loss in grain yield.